The ways to attract foreign direct investment in the economy of the Republic of Uzbekistan - Sidikova Sitora; G.Ubaydullaeva (Periodica Journal, 2022)
The article discusses the features of the development of direct foreign investment, direct controls, and direct influence of foreign direct investment. The degree of positive and negative effect of the influence of attracting foreign direct investment. Analyzed the current state of attraction foreign direct investment in the Republic of Uzbekistan.
Keywords: Foreign Direct Investment; economic crisis; competition; direct control